Omron PLC Automation Control System for Souvenir Conveyors - Sari, Mokh. Suseno Aji; Zakaria , Dimas Aji (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
Souvenirs are relatively small objects and the price is not expensive, forgifts or purchased as a memento from a place  visited,  for  example  from  a  relative's  or  relative's  wedding.  Initially,  souvenir  products  were  part  of  the handicrafts  produced  by  the  creativity  of  the  craftsmen  who  were  able  to  turn  worthless  objects  into  attractive handicraft  products,  and  were  in  great  demand  by  many  people,  especially  tourists.  Souvenirs  are  not  only handicrafts for souvenirs from a place, but have penetrated into the industry which are widely used and used in events,  activities  and  ceremonies  so  that  they  are  mass  produced.  In  everyday  life,  souvenirs  are  still  using  a manual system. PLC system development is relatively easy, has much better resistance, is cheaper, consumes less power,  detects  errors  more  easily  and  quickly, fewer  cablingsystems,  and  easy  maintenance.  PLCs  are  widely used in industrial applications such as packaging processes, material handling, automated assembly, etc. PLCs produce an output to control goods counter conveyors. A ladder diagram program that uses the CX Programmer application can be applied as commands in the PLC and produces an output that is used to drive and control the pneumatic control system on souvenirs.